SCIENTIFIC IMPACT ANALYSIS OF WATERSHED PROJECTS IN THE SRIKAKULAM DISTRICT OF ANDHRA PRADESH - P. VENKATARAMA MUNI REDDY*, K. SASIDHAR, C.P REDDY, R.V. SAGAR KUMAR REDDY; B. JANARDHAN REDDY (The Journal of Research ANGRAU, 2023)
The study was undertaken to investigate the utility of Remote sensing and Geographic information system (GIS) tools for the evaluation of four watershed projects implemented under Pradhan Mantri Krishi Sinchayee Yojana (PMKSY) project during 2011-2016 in Srikakulam district of Andhra Pradesh. The study was carried out using high resolution Resourcesat-2, Linear Imaging self-scanning sensor (LISS)-IV data of 2011 (pre-treatment) and 2016 (post-treatment) to assess the changes in land use / land cover and biomass over a period of five years (2011-16). Due to implementation of the watershed developmental activities, an additional area of 2301 ha has been brought under cultivation. The vegetation maps indicated that the areas under dense vegetation category increased by 33 percent and 62 percent of the fallow land converted to during the project period due to adoption of soil and water conservation practices. An additional area of 103 ha (2.37%) increased under water bodies and 83 ha waste land was converted to cultivable land due to construction of farm ponds, percolation tanks and check dams. This area is attributed to cropland and plantations in the year 2016-17.